2019
DOI: 10.1002/brb3.1278
|View full text |Cite
|
Sign up to set email alerts
|

Brain structural changes after multi‐strategic metamemory training in older adults with subjective memory complaints: A randomized controlled trial

Abstract: Background Metamemory is the process of monitoring and controlling one's memory. Improving metamemory may reduce the memory problem in old age. We hypothesized that metamemory training (MMT) would improve cognition in older adults with subjective memory complaints and change the brain region related to metacognition. Method We recruited and randomized older adults to the multi‐strategic memory training of 10 weekly 90‐min sessions, based on the metamemory concept or usu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 41 publications
(53 reference statements)
1
21
0
Order By: Relevance
“…Visuospatial memory and attention were not significantly different between the training and control groups. The results of the current study are similar to a previous study that noted the effects of MMT in normal older adults [6]. Youn et al found that older adults who participated in the MMT (n = 112) experienced significantly greater increases in delayed free recall and language functions (i.e., fluency, BNT) compared with the control group (n = 89).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Visuospatial memory and attention were not significantly different between the training and control groups. The results of the current study are similar to a previous study that noted the effects of MMT in normal older adults [6]. Youn et al found that older adults who participated in the MMT (n = 112) experienced significantly greater increases in delayed free recall and language functions (i.e., fluency, BNT) compared with the control group (n = 89).…”
Section: Discussionsupporting
confidence: 89%
“…Healthy older adults who participated MMT improved more substantially compared with the wait list control group in trained areas and non-trained areas [4]. A follow up study with a larger sample size of healthy adults and brain imaging replicated the transfer effects of the MMT and brain structural changes further support the initial evidence of these effects [6]. These previous results suggest that metamemory, an understanding of how memory works and monitoring of one's memory processing, could facilitate the effects of mnemonic strategies and lead to improvement of older adults' cognitive function including memory function [7,8].…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…In contrast, other assessment tools, such as Memory self-efficacy (MSE), Memory Inventory for the Chinese (MIC), and Multifactorial Memory Questionnaire (MMQ)-total score, represent great subjective memory performance when the score is high. Five studies adopted former assessment tools [30,39,40,42,43], while three used the latter [32,43,44]. In five studies, the overall effect of the cognitive training intervention on subjective memory outcome was not significant (Hedges' g = -0.11, 95% CI -0.32 to 0.10, Z = 1.01, p = 0.31).…”
Section: Cognitive Trainingmentioning
confidence: 97%
“…Five studies were categorized as lifestyle modification, with one as physical exercise [34] and four as functional foods or nutrients supplementation interventions [35][36][37][38]. Nine studies investigated the cognitive training [30][31][32][39][40][41][42][43][44] and two focused on the multidomain interventions (i.e., combined physical and mental activity, combined exercise and memory training) [45,46]. There was one study involving psychological and health-related education [47].…”
Section: Description Of Included Studiesmentioning
confidence: 99%